IMPLEMENTASI PERATURAN DAERAH NO.2 TAHUN 2012 TENTANG RETRIBUSI PARKIR DI TEPI JALAN UMUM DI KAWASAN TEMBALANG - Wikaningtyas, Alvera Hazmi; Kismartini, Kismartini; Purnaweni, Hartuti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Nowadays, Tembalang Region that have many universities there become very crowded, gives impact to the flow of traffic fluency, especially for public roadside parking that dispatch some of highroad area. Unfortunately, this condition isn’t complemeted with the revenue from public roadside levy. This reasearch is used qualitative methode and the problems on public roadside parking levy are explained descriptively with phenomenology approach. The target from Local Own Revenue (PAD) that is appointed by Semarang government never fulfilled. Parking Division of Dishubkominfo Semarang had did some efforts to decrease the revenue leakage of roadside parking levy. The large number of illegal parking spot gives much effects for the revenue target achievement. Through this Local Regulation No.2/2012 about Public Service Levies, Semarang government applies the new tariff of parking levy to fulfilled this revenue target. In this research, it can be known that Parking Division had made routine patrol to control the implementation of public roadside parking levy withdrawal. This control is conducted to againts either the illegal parking spot or illegal parking attendants. However, this illegal parking still found. In terms of completeness facilities cannot found in Tembalang Region. Meanwhile, the implementation of public roadside levy policy should be complement with equal facilities either for implementor, such parking sign facilities.